MRI Overestimates Excitotoxic Amygdala Lesion Damage in Rhesus Monkeys - Basile, Benjamin M.; Karaskiewicz, Chloe L.; Fiuzat, Emily C.; Malkova, Ludise; Murray, Elisabeth A. (Frontiers in Integrative Neuroscience, 2017)
Selective, fiber-sparing excitotoxic lesions are a state-of-the-art tool for determining the causal contributions of different brain areas to behavior. For nonhuman primates especially, it is advantageous to keep subjects with high-quality lesions alive and contributing to science for many years. However, this requires the ability to estimate lesion extent accurately. Previous research has shown that in vivo T2-weighted magnetic resonance imaging (MRI) accurately estimates damage following selective ibotenic acid lesions of the hippocampus. Here, we show that the same does not apply to lesions of the amygdala. Across 19 hemispheres from 13 rhesus monkeys, MRI assessment consistently overestimated amygdala damage as assessed by microscopic examination of Nissl-stained histological material. Two outliers suggested a linear relation for lower damage levels, and values of unintended amygdala damage from a previous study fell directly on that regression line, demonstrating that T2 hypersignal accurately predicts damage levels below 50%. For unintended damage, MRI estimates correlated with histological assessment for entorhinal cortex, perirhinal cortex, and hippocampus, though MRI significantly overestimated the extent of that damage in all structures. Nevertheless, ibotenic acid injections routinely produced extensive intentional amygdala damage with minimal unintended damage to surrounding structures, validating the general success of the technique. The field will benefit from more research into in vivo lesion assessment techniques, and additional evaluation of the accuracy of MRI assessment in different brain areas. For now, in vivo MRI assessment of ibotenic acid lesions of the amygdala can be used to confirm successful injections, but MRI estimates of lesion extent should be interpreted with caution.